Risk of myocardial infarction in critical patients over 65 years old - Barrios Morocho, Juan Luis (2017)
Introduction: Cardiovascular disease has the highest morbidity and mortality in the world. The behavior of cardiovascular disease in elderly population is poorly understood. Objective: To determine the risk of myocardial infarction in critical patients over 65 years old. Design: Cross-sectional observational study during 2014 - 2015. Participants: Patients over 65 years old. Setting: Hospital II Vitarte EsSalud, Lima, Peru. Methods: Data was collected from emergency medical records of 140 critically ill patients over 65 years old. The variables age, sex, medical history and priority of attention were analyzed. The relationships between a positive value of troponin and electrocardiographic abnormalities were detailed. The prevalence ratio and the prevalence OR were calculated. Main outcome measures: Relationship between positive value of troponin and electrocardiographic abnormalities. Results: Troponin tests in men and women above the upper reference value accounted for 50 and 60% respectively, both on admission to the emergency service and in the control obtained between 6 to 12 hours later. About 70% of patients with ischemic type alterations in the electrocardiogram (ECG) were troponin positive for myocardial necrosis. The prevalence ratio (RP) and the revalence OR (ORP) for ischemic ECG and positive troponin at admission were respectively 1.779 (CI 95%: 1.215-2.604) and 3.7 (CI 95%: 1.662- .44), respectively. For the ECG and positive troponin control, the RP was 1.969 (CI 95%: 1.345-2.884), and the ORP was 5.101 (CI 95%: 2.187-11.9). Conclusions: An increased risk of myocardial infarction was found in critical patients over 65 years old who presented electrocardiographic alterations of ischemic type during their stay in the emergency service.